Electrode film roll, electrode, and electrode laminate

A self-supporting electrode film material with a specific adhesive layer and polyisobutylene binders simplifies the manufacturing process of secondary batteries and other electrochemical devices, improving mechanical strength and adhesion, thus reducing costs and complexity.

JP2025005807APending Publication Date: 2025-01-17ZACROS CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023106185
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The manufacturing process of secondary batteries and other electrochemical devices is complex and costly due to the need for multi-step processing such as mixture preparation, coating, and pressing, which can be simplified by eliminating the use of a current collector and using a self-supporting electrode film material.

Method used

A novel electrode film material comprising an adhesive layer with specific polyisobutylene binders and a conductive material, allowing it to be used as an electrode without a current collector, and can be easily cut and pasted onto battery elements.

Benefits of technology

This approach simplifies the manufacturing process, reduces costs, and enhances the mechanical strength and adhesion of electrodes, making them easier to handle and integrate into electrochemical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025005807000004
    Figure 2025005807000004
  • Figure 2025005807000005
    Figure 2025005807000005
  • Figure 2025005807000006
    Figure 2025005807000006
Patent Text Reader

Abstract

To provide a novel electrode film roll used as a material for an electrode, and an electrode and an electrode laminate using such an electrode film roll as a material.SOLUTION: An electrode film roll includes an adhesive layer and a positive electrode active material layer laminated with the adhesive layer, and the positive electrode active material layer including a positive electrode active material. The adhesive layer contains a particulate conductive material and a binder. The binder contains a first polyisobutylene having a viscosity average molecular weight of 1 million or more and a second polyisobutylene having a viscosity average molecular weight of 10,000 or more and 100,000 or less. The conductive material is a carbon material, and the adhesive layer contains 15 mass% or more and 25 mass% or less of the conductive material, 25 mass% or more and 50 mass% or less of the first polyisobutylene, and 30 mass% or more and 60 mass% or less of the second polyisobutylene relative to 100 mass% of the combined total of the conductive material and the binder.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrode film substrate, an electrode, and an electrode laminate. [Background technology]

[0002] In recent years, the importance of secondary batteries as power sources has increased. Research and development of secondary batteries has been actively conducted, from small ones such as power sources for portable electronic devices to medium and large ones such as electric vehicles and home storage batteries.

[0003] A secondary battery has a pair of electrodes containing active materials and an electrolyte disposed between the electrodes. The pair of electrodes includes a positive electrode containing a positive electrode active material and a negative electrode containing a negative electrode active material. As these electrodes, a configuration in which an active material layer containing a positive electrode active material or a negative electrode active material and a current collector having excellent electrical conductivity are laminated is known.

[0004] The active material layer is formed by dispersing a powdered active material and a binder in a solvent to prepare a slurry mixture, applying the mixture onto a current collector, and pressing the mixture. The laminate of the active material layer and the current collector is cut into a desired battery shape and used as an electrode (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2019-169444 A Summary of the Invention [Problem to be solved by the invention]

[0006] As described above, in order to prepare an electrode, multi-step processing is required, such as preparation of a mixture, coating of the mixture, drying, pressing, etc. In order to simplify the manufacturing process of a secondary battery and reduce the manufacturing cost, there is room for improvement in terms of materials.

[0007] The same problem may occur not only in secondary batteries but also in other electrochemical elements such as capacitors.

[0008] The present invention has been made in view of the above circumstances, and has an object to provide a novel electrode film raw material used as a material for electrodes, and a further object to provide an electrode and an electrode laminate using such an electrode film raw material as a material. [Means for solving the problem]

[0009] The inventors considered that if they could realize a material that has sufficient mechanical strength and has properties that allow it to be used as an electrode without using a current collector, it would be possible to design more efficient electrochemical devices and omit steps such as coating the current collector with a mixture. In addition, by forming the material into a film shape, it would be possible to easily manufacture an electrochemical device by cutting the film (electrode film raw material) and attaching it to a battery element.

[0010] In order to solve the above problems, one aspect of the present invention includes the following aspects.

[0011] [1] An electrode film base roll comprising: an adhesive layer; and a positive electrode active material layer laminated with the adhesive layer and containing a positive electrode active material, wherein the adhesive layer contains a particulate conductive material and a binder, the binder containing a first polyisobutylene having a viscosity average molecular weight of 1 million or more and a second polyisobutylene having a viscosity average molecular weight of 10,000 or more and 100,000 or less, the conductive material being a carbon material, and the adhesive layer containing, relative to 100% by mass of the combined weight of the conductive material and the binder, 15% by mass or more and 25% by mass or less of the conductive material, 25% by mass or more and 50% by mass or less of the first polyisobutylene, and 30% by mass or more and 60% by mass or less of the second polyisobutylene.

[0012] [2] The electrode film base material according to [1], which has a breaking strength of 0.4 MPa or more, measured by the following measurement method, and an elongation percentage at the time of exhibiting said breaking strength of 3% or more and 7% or less. (Measurement method) The electrode film raw material was cut to a size of 15 mm in width and 50 mm in length to obtain a test piece, and the strength at 75% of the maximum stress when measured under conditions of a chuck distance of 30 mm and a tensile speed of 100 mm / min was defined as the breaking strength.

[0013] [3] The electrode film base sheet according to [1] or [2], wherein the adhesive layer has a breaking strength of 0.3 MPa or more, as measured by the following measurement method, and an elongation percentage at the time of exhibiting the breaking strength of 30% or more. (Measurement method) The electrode film raw material was cut to a size of 15 mm in width and 50 mm in length to obtain a test piece, and the strength at 75% of the maximum stress when measured under conditions of a chuck distance of 30 mm and a tensile speed of 100 mm / min was defined as the breaking strength.

[0014] [4] The electrode film substrate according to any one of [1] to [3], wherein the adhesive layer has an adhesive strength of 0.05 N / cm or more in a 90° peel test performed by the following measurement method. (Measurement method) The adhesive layer side of a test piece 15 mm wide and 50 mm long cut from the electrode film roll is attached to the center of an Al foil 15 mm wide and 60 mm long. A paper tape longer than the test piece is attached to the side of the test piece opposite the adhesive layer side, and the strength is measured when the paper tape protruding from the test piece is grasped and the test piece together with the paper tape is peeled off at 90° at a speed of 20 mm / min. The same measurement is performed three times, and the arithmetic average of the measured values ​​is taken as the adhesive strength. (Lamination conditions) Roll lamination at a pressure of 8.6 kg / cm, speed of 1 m / min, and 25°C.

[0015] [5] The electrode film base material according to any one of [1] to [4], wherein a release film is laminated on the adhesive layer.

[0016] [6] An electrode made from the electrode film base material described in any one of [1] to [5].

[0017] [7] An electrode laminate comprising the electrode according to [6] and any one selected from the group consisting of a current collector foil, a separator, and a solid electrolyte membrane.

[0018] [8] An electrode laminate comprising the electrode according to [6], a first member laminated on a first surface of the electrode, and a second member laminated on a second surface of the electrode, wherein the first member and the second member are each any one selected from the group consisting of a current collector foil, a separator, and a solid electrolyte membrane. Effect of the Invention

[0019] According to the present invention, it is possible to provide a novel electrode film raw material used as a material for an electrode, and also to provide an electrode and an electrode laminate using such an electrode film raw material as a material. [Brief description of the drawings]

[0020] [Figure 1] FIG. 1 is a schematic diagram showing an original electrode film 1 of the present embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing an original electrode film 2 of the present embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing an electrode laminate 100. As shown in FIG. [Figure 4] FIG. 4 is a schematic diagram showing an electrode stack 150 and a cell 500 having the electrode stack 150. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] {Electrode film roll, electrodes} 1 is a schematic diagram (cross-sectional view) showing an electrode film raw material 1 of the present embodiment. The electrode of the present embodiment is made of the electrode film raw material 1.

[0022] The term "electrode film raw material" refers to a film-like molded product before being processed into an electrode. Typically, the electrode film raw material is a long molded product formed into a belt-like shape, or a sheet-like molded product obtained by processing such a belt-like molded product into sheets.

[0023] 1 is sandwiched from both sides between release films 10. As the release film 10, a known material such as a PET film that has been subjected to a release treatment can be used.

[0024] Although the electrode film raw material 1 in FIG. 1 has release films 10 on both sides, it may also be configured so that the release film 10 is provided only on the adhesive layer 11 .

[0025] The electrode film raw material 1 is a laminate of an adhesive layer 11 and a positive electrode active material layer 12. The electrode film raw material 1 does not have a current collector.

[0026] The electrode film raw material 1 has the characteristic functions of (a) having adhesiveness, (b) being self-supporting, and (c) being usable as an electrode.

[0027] (a) Adhesive properties "Adhesiveness" means that the electrode film can be attached to other materials due to its surface properties without the use of a separate adhesive or pressure sensitive adhesive. The electrode film raw material 1 is cut into a desired shape and processed into an electrode, and then attached to, for example, a solid electrolyte plate material to function as an electrode for a solid-state battery.

[0028] (b) Become independent The electrode film raw roll 1 can be processed into an electrode by cutting it into a desired shape. The electrode film raw roll 1 may be used as an electrode as it is. The resulting electrode can maintain the cut shape without having any attachments such as a base material. In this specification, the presence of such a property is sometimes referred to as "self-supporting" or "self-supporting type." In other words, the electrode film raw roll 1 has the rigidity to exist without support.

[0029] (c) Can be used as an electrode The electrode film raw roll 1 can be cut into a desired shape and used as an electrode for electrochemical devices such as secondary batteries and capacitors. In this specification, the suitability of the electrode film raw roll 1 for use as an electrode is determined by the SOC (State of Charge)-OCV (Open Circuit Voltage) value.

[0030] The electrode obtained by cutting the electrode film raw roll 1 having the functions of (a) and (c) can simplify the process of attaching it to the components of an electrochemical device, and can be used as an electrode for such electrochemical devices simply by attaching it to the components of the electrochemical device such as secondary batteries and capacitors. In addition, by having the function of (b), it is self-supporting (a self-supporting electrode) and can be easily processed.

[0031] Hereinafter, each component of the electrode film raw material 1 will be described in order.

[0032] [Structure of electrode film roll] The electrode film raw material 1 has a laminated structure of an adhesive layer 11 and a positive electrode active material layer 12. Although details will be described later, as an example, the electrode film raw material 1 can be produced by laminating a film corresponding to the adhesive layer 11 and a film corresponding to the positive electrode active material layer 12.

[0033] (adhesive layer) The adhesive layer 11 includes a particulate conductive material and a binder. The adhesive layer 11 may further include a positive electrode active material.

[0034] The adhesive layer 11 has a relatively high adhesive strength compared to the positive electrode active material layer 12. Moreover, the adhesive layer 11 has a relatively higher strength than the positive electrode active material layer 12 in order to ensure the mechanical strength of the electrode film raw material 1, which is a laminate.

[0035] In order to achieve such physical properties, the binder constituting adhesive layer 11 includes a first polyisobutylene having a viscosity average molecular weight of 1 million or more, and a second polyisobutylene having a viscosity average molecular weight of 10,000 or more and 100,000 or less. In detail, the adhesive layer includes 15% by mass or more and 25% by mass or less of the conductive material, 25% by mass or more and 50% by mass or less of the first polyisobutylene, and 30% by mass or more and 60% by mass or less of the second polyisobutylene, relative to 100% by mass of the combined weight of the conductive material and the binder.

[0036] In the adhesive layer 11, the conductive material is preferably 15% by mass or more and 30% by mass or less.

[0037] In the adhesive layer 11, the first polyisobutylene is preferably from 28% by mass to 48% by mass, and more preferably from 30% by mass to 45% by mass.

[0038] In the adhesive layer 11, the second polyisobutylene is preferably present in an amount of 33 mass % or more and 58 mass % or less, and more preferably 35 mass % or more and 55 mass % or less.

[0039] The viscosity average molecular weight of the first polyisobutylene is preferably from 1 million to 10 million, more preferably from 1 million to 5 million. As such polyisobutylene, commercially available polyisobutylene (e.g., manufactured by BASF, model number N150, viscosity average molecular weight 2,600,000 (manufacturer's nominal value)) can be used.

[0040] The viscosity average molecular weight of the second polyisobutylene is preferably from 10,000 to 100,000, and more preferably from 10,000 to 50,000. As such polyisobutylene, commercially available polyisobutylene (for example, manufactured by ENEOS Corporation, model number 6T, viscosity average molecular weight 30,000 (manufacturer's nominal value)) can be used.

[0041] Assume that a third polyisobutylene having a molecular weight equivalent to that of a mixture of the first polyisobutylene and the second polyisobutylene is used as a binder. This third polyisobutylene has a smaller viscosity average molecular weight than the first polyisobutylene and a larger viscosity average molecular weight than the second polyisobutylene. However, the inventors have confirmed through their studies that when the third polyisobutylene (binder) is kneaded with a conductive material, the conductive material is difficult to disperse and ends up agglomerating.

[0042] On the other hand, when the binder is a mixture of a first polyisobutylene and a second polyisobutylene having different viscosity average molecular weights, dispersion of the conductive material can be promoted when the binder and the conductive material are kneaded together.

[0043] The conductive material is in the form of particles and is dispersed in the adhesive layer. The conductive material contained in the adhesive layer is a carbon material.

[0044] Examples of the carbon material include known materials such as carbon black, such as acetylene black and ketjen black, carbon fiber, activated carbon, and carbon nanotubes (CNT).

[0045] As the carbon material, commercially available acetylene black (for example, manufactured by Alfa Aesar, model number 45527) or commercially available ketjen black (for example, manufactured by Lion Specialty Chemicals, model number EC600JD) can be used.

[0046] The conductive material used has a volume average particle size of 0.1 to 100 μm.

[0047] The adhesive layer 11 may contain other binders as long as the effects of the invention are not impaired. Examples of the other binders include the binders constituting the positive electrode active material layer described below.

[0048] (Cathode active material layer) The positive electrode active material layer 12 contains a positive electrode active material and a binder.

[0049] (active material) As the active material, a powdered material known as a positive electrode active material for secondary batteries or a positive electrode active material for capacitors can be used.

[0050] When a lithium ion secondary battery is used as the secondary battery, the positive electrode active material of the lithium ion secondary battery may be at least one selected from composite oxides of lithium and transition metals such as cobalt, manganese, nickel, etc., polymers having Li storage capacity, etc. The positive electrode active material of the lithium ion secondary battery may be any compound that can reversibly dope and dedope lithium ions.

[0051] For example, lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMnO4), lithium iron phosphate (LiFePO4), Ni-Mn-Co ternary (NMC) active material (LiNi x Mn y Co z O2), Ni-Co-Al ternary system (NCA system) active material (LiNi x Co y Al z O2) etc.

[0052] The active material for lithium ion secondary batteries has a volume average particle size of 0.1 to 100 μm.

[0053] When a lithium ion capacitor is used as the capacitor, examples of the positive electrode active material of the lithium ion capacitor include carbon-based materials such as activated carbon and polymers with Li storage capacity. The positive electrode active material of the lithium ion capacitor may be any material that can reversibly dope and dedope lithium ions.

[0054] The active material for the lithium ion capacitor has a volume average particle size of 0.1 to 100 μm.

[0055] (binder) The positive electrode active material layer 12 may be a known positive electrode active material layer that does not stand on its own by itself. In this case, polyvinylidene fluoride (PVdF) can be used as a binder for the positive electrode active material layer 12.

[0056] The positive electrode active material layer 12 may be a layer that is self-supporting by containing the following binder.

[0057] The binder is a material used to bind particles of the active material, etc., and is, for example, a resin. As the binder, a known thermoplastic resin used for the above-mentioned purpose as an electrode material can be used.

[0058] In addition to the above-mentioned "binding of particles of active material, etc.", the functions of the binder include (i) imparting high strength to the electrode film roll, (ii) making it easier to adhere an electrode made from the electrode film roll to other components, and (iii) adjusting other physical properties. (ii) is not essential for the above-mentioned functions (a) and (c) required for a "self-supporting electrode," but is important for achieving the above-mentioned function (b). Binders that have a particularly strong function of (i) will be described as "high-strength binders," binders that have a particularly strong function of (ii) as "adhesive binders," and (iii) as "other binders."

[0059] In the electrode film raw sheet 1 of the present embodiment, the adhesive layer 11 has the above function (ii). Here, it will be explained that the binder constituting the positive electrode active material layer 12 contains the above adhesive binder, which makes it easier to adhere to other members on the surface on the positive electrode active material layer side.

[0060] (i) High-strength binder An elastomer can be used as the high-strength binder. A binder having elastomeric properties can impart flexibility and strength to the electrode, and can suppress breakage caused by volumetric changes in the active material when the electrode is used.

[0061] It is desirable for the high-strength binder to have a breaking strength of 5 MPa or more. Furthermore, the high-strength binder is required to be stable to the electrolyte inside the electrochemical element (battery, capacitor) and is required to be electrochemically stable.

[0062] For example, when a lithium ion battery is employed as the electrochemical element and an electrode obtained by cutting the electrode film roll 1 is used, the high-strength binder is required not to dissolve from the electrode into the electrolyte filled in the battery. In addition, when the electrode is used as the positive electrode, the high-strength binder is required not to be oxidatively decomposed at 3 to 5 V (vs. Li / Li+).

[0063] The tensile strength of the high-strength binder is a value measured by the breaking strength measuring method described below.

[0064] As the binder, a copolymer containing styrene and a conjugated diene can be used. Such a copolymer is Styrene-butadiene copolymer (SBR) Styrene-isoprene copolymer Styrene-butadiene-methyl methacrylate copolymer (MBS) · Acrylonitrile-styrene-butadiene copolymer (ABS) Acrylonitrile-styrene-butadiene-methyl methacrylate copolymer (MABS) Carboxylic modified styrene butadiene rubber Styrene-butadiene-styrene block copolymer (SBS) Styrene-isoprene-styrene block copolymer (SIS) Styrene-isoprene-butadiene-styrene block copolymer (SIBS) Examples include:

[0065] The copolymer may contain other copolymerizable vinyl monomers.

[0066] Vinyl monomers include: · Acrylate monomers such as alkyl acrylate Methacrylate monomers such as alkyl methacrylate · Acrylamide monomers such as alkoxyacrylamides Methacrylamide monomers such as alkoxymethacrylamides Carboxylic acid monomers such as acrylic acid Nitrile monomers such as acrylonitrile Vinyl ester monomers such as vinyl acetate Vinyl chloride and other vinyl halide monomers · Polyfunctional monomers such as allyl acrylate Examples include: One or more of these vinyl monomers may be copolymerized in the copolymer.

[0067] ((ii) Adhesive Binder) The adhesive binder can be a resin material with reactive functional groups or an anchor effect. Examples of reactive functional groups include hydroxyl groups (-OH) and carboxyl groups (-COOH). If the electrode film raw roll contains such a binder, when the electrode obtained from the electrode film raw roll is laminated to another component, the reactive functional groups are expected to react at the lamination surface, thereby increasing the adhesive strength.

[0068] Furthermore, when the electrode film raw sheet contains an adhesive binder, a free-standing electrode produced from the electrode film raw sheet is more likely to exhibit the above function (ii).

[0069] It is desirable for the adhesive binder to be electrochemically stable and to have adhesive properties even when exposed to other members, particularly the electrolyte.

[0070] For example, when a lithium ion battery is employed as the electrochemical element and an electrode obtained by cutting an electrode film roll 1 is used, the adhesive binder is required not to dissolve from the electrode into the electrolyte filled in the battery, and the reactive functional groups are required not to be deactivated even when exposed to the electrolyte.

[0071] When the above electrode is used as a positive electrode, the adhesive binder is required not to undergo reductive decomposition at 3 to 5 V (vs. Li / Li+).

[0072] Such a binder may be at least one selected from the group consisting of carboxymethyl cellulose (CMC)-based binders, polyacrylic acid (PAA)-based binders, vinyl alcohol-based binders, and epoxy-based binders.

[0073] Also, polyisobutylene (PIB) can be used as the adhesive binder.

[0074] ((iii) Other binders) Further examples of binders that can be used in combination include acrylate-based binders, polyvinylidene fluoride (PVdF)-based binders, and polyimide-based binders. These binders can make up for the lack of functionality of the electrode. For example, (i) high-strength binders are considered to be electrochemically inactive, and if the active material is completely covered with (i) high-strength binders, the electrochemical reaction of the active material will not occur and the resistance of the electrode will increase. In contrast, by using (iii) other binders as described above in combination, it is considered that the increase in resistance caused by covering the active material with an inactive binder can be suppressed.

[0075] The blending ratio of the above binders (i) to (iii) is adjusted according to the desired physical properties based on the following guidelines.

[0076] (i) The high-strength binder mainly plays a role in binding the active material in the electrode (electrode film raw material). Therefore, the amount of (i) the high-strength binder is adjusted in a positive correlation with the amount of the active material used.

[0077] In addition, (i) the high-strength binder can impart flexibility and strength to the electrode when used in greater amounts relative to the active material. Furthermore, some (i) high-strength binders exhibit adhesive properties.

[0078] (ii) The adhesive binder imparts adhesiveness to the electrode film roll. Since the adhesiveness of an electrode is determined by the amount of adhesive binder present per unit area (unit volume), the adhesiveness of the electrode improves as the amount of (ii) adhesive binder used increases.

[0079] (iii) Other binders are added as necessary to compensate for insufficient functions of the electrode.

[0080] Furthermore, in addition to the above-mentioned active material and binder, the positive electrode active material layer 12 may contain additives such as conductive materials as necessary to adjust the physical properties. The conductive materials include at least one selected from carbon black such as acetylene black, carbon fiber, activated carbon, metal powder, conductive polymers, etc. The conductive material does not need to have activity like the active material, and may be a material that improves the conductivity inside the electrode.

[0081] The mixture constituting the electrode film raw sheet may contain carbon nanotubes (CNTs). An electrode film raw sheet containing CNTs is expected to have improved breaking strength and electrical conductivity.

[0082] (Electrode film roll) The thickness of the electrode film raw material 1 is preferably 1 μm or more and 1000 μm or less.

[0083] The adhesive layer 11 preferably occupies 10% to 20% by volume of the electrode film raw material 1. The positive electrode active material layer 12 preferably occupies 80% to 90% by volume of the electrode film raw material 1.

[0084] The adhesive layer 11 configured as described above is relatively more deformable and stretchable than the positive electrode active material 12. Therefore, when stress is applied to the electrode film raw material 1, even if a stress strong enough to break the positive electrode active material layer 12 is applied, the adhesive layer 11 does not break and the electrode film raw material 1 can maintain its overall shape (stand by itself).

[0085] The electrode film raw roll 1 may satisfy the following requirements (1) and (3) in order to realize the above-mentioned functions of (a) having adhesiveness and (c) being usable as an electrode. Furthermore, the electrode film raw roll 1 may satisfy the following requirement (2) in order to realize the above-mentioned function of (b) being self-supporting.

[0086] (Requirement (1)) The adhesive layer 11 of the electrode film raw material 1 has an adhesive strength of 0.05 N / cm or more in a 90° peel test. The electrode film raw material 1 that satisfies the requirement (1) has the above-mentioned feature of "(a) having adhesiveness".

[0087] (Method of measuring adhesive strength) The adhesive layer side of a test piece 15 mm wide and 50 mm long cut from the electrode film roll is attached to the center of an Al foil 15 mm wide and 60 mm long under the following conditions. (Lamination conditions) Roll lamination at a pressure of 8.6 kg / cm, speed of 1 m / min, and 25°C.

[0088] In detail, the electrode film raw roll is cut to a width of 50 mm and a length of 150 mm, and is laminated to an Al foil having a width of 60 mm and a length of 200 mm under the above lamination conditions. While maintaining the short-side dimensions of the obtained laminate, the laminate is cut into multiple pieces in the longitudinal direction to obtain a laminate in which an Al foil having a width of 15 mm and a length of 60 mm (the width of the original Al foil) is laminated with an Al foil having a width of 15 mm and a length of 50 mm (the width of the original electrode film). A paper tape longer than the test piece is laminated to the laminate on the side opposite to the adhesive layer side of the test piece. The paper tape is used to prevent the adhesive layer from stretching due to traction during the test and to appropriately measure the adhesive strength. It is advisable to select a paper tape with appropriate rigidity depending on the purpose.

[0089] The obtained laminate was attached to a ring core with a diameter of 11 cm from the Al foil side, and a 90° peel test was performed by grasping the paper tape protruding from the test piece and pulling the electrode film part together with the paper tape at a speed of 20 mm / min. The adhesive strength can be calculated as the value (N / cm) obtained by dividing the peel force (N) when peeling the electrode film from the metal foil by the width (cm) of the electrode film.

[0090] The peel test is carried out three times, and the arithmetic mean value of the three measured values ​​is used as the adhesive strength.

[0091] As described above, the adhesive strength can be obtained by the peel test to judge whether or not the requirement (1) is satisfied.

[0092] The adhesive layer having such adhesive strength makes it easy to attach the electrode obtained from the electrode film roll to other members and prevents the electrode from peeling off due to its own weight. This makes the subsequent assembly process easier. In addition, the attached electrode is less likely to peel off, improving the reliability of the resulting electrochemical device.

[0093] The ratio of the binder to the entire mixture may be adjusted according to the physical properties required for the electrode film raw material to be formed. When attaching importance to the adhesive strength of the electrode to other members such as a separator for the electrode to be manufactured from the electrode film raw material, the binder content may be increased within the above range. When attaching importance to the electrical properties of the electrode, the binder content may be decreased within the above range.

[0094] (Requirement (2)) As described above, the electrode film raw material 1 preferably has the characteristic of "(2) being self-supporting." The electrode film raw material 1 having such rigidity has a breaking strength of 0.4 MPa or more, as measured by the following measurement method, and an elongation percentage at the time of exhibiting the breaking strength of 3% or more and 7% or less.

[0095] (Method of measuring breaking strength and elongation) The electrode film roll is cut into a test piece having a width of 15 mm and a length of 50 mm, and the test piece is measured under the conditions of a chuck distance of 30 mm and a tensile speed of 100 mm / min. The strength at 75% of the maximum stress is defined as the breaking strength.

[0096] The elongation percentage is calculated from the chuck distance of the test piece when it exhibits breaking strength, according to the following formula (1). Elongation rate (%) = (L1-L0) / L0 × 100 … (1) L0: Initial chuck distance (30mm) L1: Distance between chucks when breaking strength is shown

[0097] The magnitude of the tensile force (N) when the test piece breaks is taken as the maximum stress, and the stress at 75% of the maximum stress is calculated. The 75% stress (N) is multiplied by the cross-sectional area (mm 2 ) divided by (N / mm 2 = MPa) is calculated as the breaking strength.

[0098] The measurement is carried out three times, and the arithmetic mean value of the three measurements is used as the breaking strength.

[0099] When the electrode film raw sheet has such breaking strength, the electrodes cut from the electrode film raw sheet can be made to stand on their own. Making the electrodes stand on their own makes it easier to handle the electrodes in the subsequent assembly process.

[0100] The breaking strength is preferably 0.6 MPa or more, more preferably 0.7 MPa or more. In addition, the higher the breaking strength, the more difficult it is to break, so it can be said to be preferable, but it is sufficient that the breaking strength is 10 MPa or less, and may be 5 MPa or less.

[0101] In addition, the electrode film raw roll 1 has the characteristic of maintaining its shape and performance as a positive electrode against volumetric changes during charging and discharging. Since the electrode film raw roll 1 has an elongation rate of 3% or more when it exhibits breaking strength, it is less susceptible to deterioration due to volumetric changes in the positive electrode active material during charging and discharging, and the performance of the positive electrode cut from the electrode film raw roll can be easily maintained.

[0102] The measurement is carried out three times, and the arithmetic mean value of the three measurements is used as the elongation percentage.

[0103] The elongation is preferably 4% or more, and more preferably 5% or more.

[0104] Furthermore, the adhesive layer preferably has a breaking strength of 0.3 MPa or more as determined by the method described above (Method of measuring breaking strength and elongation), and an elongation at which the breaking strength is exhibited of 30% or more.

[0105] The breaking strength of the adhesive layer is preferably 0.6 MPa or more, more preferably 0.7 MPa or more. The higher the breaking strength, the more difficult it is to break, so it is preferable, but it may be 10 MPa or less, or may be 5 MPa or less.

[0106] The elongation percentage of the adhesive layer is preferably 20% or more, more preferably 30% or more, and may be 600% or less, or may be 500% or less.

[0107] By including a positive electrode active material in the adhesive layer, the adhesive layer can also partially function as a positive electrode active material layer. On the other hand, the elongation rate of the adhesive layer tends to decrease when the adhesive layer includes a positive electrode active material. Therefore, when the adhesive layer includes a positive electrode active material, in order to provide technical significance to the inclusion of the positive electrode active material, it is preferable to include the positive electrode active material to an extent that the elongation rate is 150% or less.

[0108] (Requirement (3)) As described above, the electrode film raw material roll 1 has the characteristic of being “(c) usable as an electrode.” As described above, whether the electrode film raw material roll 1 can be used as an electrode is determined by the SOC-OCV value.

[0109] (Preparation of coin cells for measurement) A test electrode made from an electrode film roll is placed on the bottom cover of the coin cell R2032. A separator (Celgard 2300, manufactured by Celgard) is placed on the test electrode, and then an electrolyte (1 mol / L solution of LiPF6) is poured in. The electrolyte solvent is a mixed solvent of ethylene carbonate, diethyl carbonate, and ethyl methyl carbonate in a 1:1:1 (volume ratio).

[0110] A counter electrode (metallic lithium) is placed on the separator, and the cell is then covered with a lid. The cell is then left to stand for 12 hours to completely soak in the electrolyte, producing a lithium secondary battery (coin cell for measurement).

[0111] (Method of measuring SOC-OCV value) The amount of active material contained in a test electrode prepared from an original sheet of electrode film is calculated, and the theoretical capacity (mAh / g) of the test electrode is determined from the theoretical capacity of the active material and the amount of active material. Next, the measurement coin cell is charged at 0.1 C for 30 minutes and then rested for 5 minutes, and the same operation is repeated a total of 22 times. The number of charges until the voltage reaches 0.05V is taken as the SOC-OCV value.

[0112] In this specification, when the SOC-OCV value measured by the above method is 18 times or more, it is determined that the electrode is sufficiently usable.

[0113] When the electrode film raw material exhibits such an SOC-OCV value, the electrode obtained from the electrode film raw material functions satisfactorily as a battery.

[0114] Furthermore, the volume resistance value of the electrode film raw sheet 1 is preferably 80 mΩ or less. The electrical resistance of the electrode film raw sheet 1 can be measured by the following method.

[0115] (Method of measuring volume resistivity) First, the main surfaces of a pair of Cu blocks are placed together and a weight of 2 kg is applied to perform zero-point calibration. The Cu blocks used have main surfaces of 30 × 30 mm and a thickness of 20 mm.

[0116] Next, a test piece of the electrode film original sheet sandwiched between Al foil was placed between the main surfaces of a pair of Cu blocks and a weight of 2 kg was applied. The test piece and Al foil were 30 × 30 mm in plan view, the same as the main surfaces of the Cu blocks.

[0117] The resistance after 2 minutes is then measured and used as the electrical resistance of the test piece. The electrical resistance is measured, for example, using a Battery HiTester (model number: BT3562, manufactured by Hioki E.E. Corporation).

[0118] When comparing the volume resistance values ​​of different electrode film raw rolls, the test pieces to be compared are made to have the same thickness. The thickness of the electrode film raw roll can be controlled by the method described in the manufacturing method described below.

[0119] When a positive electrode active material layer is formed by applying a slurry containing a positive electrode active material onto an object (e.g., a current collector) and compressing the coating, the interface between the positive electrode active material layer and the object is considered to be sufficiently adhered, and the interface resistance is considered to be sufficiently low. On the other hand, when the positive electrode active material layer is attached to the object via a free-standing adhesive layer as in the present invention, the adhesion of the interface between the adhesive layer and the object is insufficient compared to the above-mentioned coating, and the interface resistance is likely to be large. In addition, the interface between the positive electrode active material layer and the adhesive layer is also considered to be a cause of interface resistance.

[0120] Therefore, in the present invention, when the electrical resistance is measured by the above-mentioned method and the volume resistance is found to be 80 mΩ or less, it is determined that a sufficiently small interfacial resistance has been achieved.

[0121] [Manufacturing method of electrode film roll] The electrode film raw material can be produced by applying a slurry (paint) in which the above-mentioned mixture is dissolved or dispersed in a solvent onto a support, removing the solvent to produce a film corresponding to the adhesive layer 11 and a film corresponding to the positive electrode active material layer 12, and then laminating the obtained films together.

[0122] The solvent to be used is one that dissolves at least the binder. Examples of the solvent include hydrocarbon solvents, alcohol solvents, ether solvents, ketone solvents, ester solvents, amide solvents, halogen solvents, sulfur solvents, and inorganic solvents.

[0123] Examples of the hydrocarbon solvent include heptane, cyclohexane, toluene, and xylene.

[0124] Examples of the alcohol solvent include methanol and ethanol.

[0125] Examples of the ether solvent include tetrahydrofuran and dioxane.

[0126] Examples of the ketone solvent include acetone and methyl ethyl ketone.

[0127] Examples of the ester solvent include ethyl acetate and ethyl lactate.

[0128] Examples of the amide solvent include dimethylformamide and N-methyl-2-pyrrolidone.

[0129] Examples of halogen-based solvents include chloroform and dichloromethane.

[0130] Examples of sulfur-based solvents include dimethyl sulfoxide and sulfolane.

[0131] An example of the inorganic solvent is water.

[0132] The above solvents may be used alone or in the form of a mixed solvent of two or more kinds.

[0133] The method for preparing the coating material is not particularly limited, and may be such that the active material, binder, optional additives, etc. are mixed with a solvent one by one or two or more at the same time, and dissolved or dispersed in the solvent.

[0134] There is no restriction on the order of adding solids (active material, binder, optional additives) to the solvent. The insoluble components may be added to a solution in which the soluble components are dissolved in a solvent, and the insoluble components may be dispersed in the solution. Alternatively, the soluble components may be added to a dispersion in which the insoluble components are dispersed in a solvent, and the soluble components may be dissolved in the dispersion.

[0135] After preparing the slurry or solution, further solvent may be added to adjust the viscosity of the coating material.

[0136] The condition of the paint may be adjusted by treatment such as defoaming, filtration, etc. Additives such as defoamers, viscosity adjusters, thickeners, diluents, surfactants, stabilizers, etc. may be added to the paint.

[0137] The method for applying the coating material is not particularly limited, but examples thereof include blade coating, dip coating, spray coating, bar coating, and die coating.

[0138] The object to be coated with the paint (support) is preferably a release-treated resin film. The support may be a long strip, or a small sheet obtained by processing a long support into sheets.

[0139] By removing the solvent from the coating film formed by applying the paint, it is possible to form a film corresponding to the adhesive layer 11 and a film corresponding to the positive electrode active material layer 12. The solvent can be removed by heating, reducing pressure, blowing air, or a combination of these.

[0140] The dried coating film may be subjected to press processing. For example, by compressing the dried coating film with a press or the like, the contact state of particles of the active material, conductive material, and the like contained in the electrode can be improved.

[0141] An electrode film raw material can be manufactured by laminating the obtained films together (a film corresponding to the adhesive layer 11 and a film corresponding to the positive electrode active material layer 12). When laminating, it is preferable to perform a press working.

[0142] When a long, strip-shaped support is used, the electrode film raw material may be wound into a roll for storage and transportation, or may be further processed into a plurality of sheet-shaped electrode film raw materials by sheet processing.

[0143] In this manner, the electrode film raw material 1 is obtained.

[0144] FIG. 2 is a schematic diagram showing an original electrode film 2 of the present embodiment. 2 has an adhesive layer 21, a positive electrode active material layer 22, and a functional layer 25. The electrode film raw material 2 is also sandwiched between release films 10 on both sides. The adhesive layer 21 and the positive electrode active material layer 22 can have the same configuration as the adhesive layer 11 and the positive electrode active material layer 12 described above, respectively.

[0145] Although the electrode film raw material 2 in FIG. 2 has release films 10 on both sides, it may also be configured so that the release film 10 is provided only on the adhesive layer 21 .

[0146] The electrode film substrate 2 does not have a current collector.

[0147] The mixture constituting the adhesive layer 21 and the positive electrode active material layer 22 can be the same as the mixture constituting the electrode film substrate 1 described above.

[0148] The functional layer 25 is provided in contact with the surface of the positive electrode active material layer 22 opposite to the adhesive layer 21. There are no particular limitations on the functional layer 25 as long as it is a layer that is added for the purpose of improving the function of the electrode. Examples of the functional layer 25 include a heat dissipation layer, a planarization layer, a stress relaxation layer, and an adhesion layer.

[0149] The electrode film raw roll 2 can be produced by producing the adhesive layer 21 and the positive electrode active material layer 22 corresponding to the electrode film raw roll 1 in the same manner as the above-mentioned electrode film raw roll 1, and then producing the functional layer 25 on the surface of the positive electrode active material layer 22. The functional layer 25 can be appropriately produced by using a known material and a known method.

[0150] According to the electrode film raw material having the above-mentioned configuration, it is possible to provide a novel electrode film raw material used as an electrode material.

[0151] Furthermore, the electrode having the above-mentioned structure has sufficient adhesive strength and is easy to handle when assembling a battery.

[0152] [Electrode laminate] 3 is a schematic diagram (cross-sectional view) showing an electrode laminate 100. The electrode laminate 100 is a laminate in which an electrode 110 and any one layer 120 selected from the group consisting of a current collector foil, a separator, and a solid electrolyte membrane are laminated together. The electrode 110 has the same configuration as the electrode produced from the electrode film raw roll 1 described above, and is a laminate of an adhesive layer 11 and a positive electrode active material layer 12. The electrode 110 is bonded to the layer 120 at the adhesive layer 11.

[0153] When the electrode laminate 100 is incorporated into a battery or a capacitor, the electrode 110 functions as a positive electrode.

[0154] When layer 120 is a separator, the electrode laminate 100 of positive electrode 110 and separator is primarily used in electrochemical devices that use electrolytes.

[0155] The separator is a material that insulates the positive electrode from the negative electrode and has ion permeability necessary for the function of the electrodes. The separator is not particularly limited, and known resin films, porous membranes, etc. can be used.

[0156] Examples of the resin film include polypropylene, polyethylene, polyolefin, aramid, polyvinylidene fluoride, polyacrylonitrile, polyimide, polyamide, polyethersulfone, etc. The resin film may be made porous in order to impart ion permeability.

[0157] Porous membranes include woven fabric, nonwoven fabric, cellulose, ceramic, and the like.

[0158] When the layer 120 is a solid electrolyte membrane, the electrode laminate 100 of the positive electrode 110 and the solid electrolyte membrane is used in an all-solid-state secondary battery, which is a type of electrochemical device.

[0159] The solid electrolyte membrane is a member obtained by processing a commonly known solid electrolyte into a plate or film shape. As the material for the solid electrolyte membrane, any of commonly known inorganic solid electrolytes and polymer solid electrolytes can be used.

[0160] As the inorganic solid electrolyte, any of sulfide-based inorganic solid electrolytes, oxide-based inorganic solid electrolytes, and other lithium-based inorganic solid electrolytes can be used.

[0161] Examples of the sulfide-based inorganic solid electrolyte include Li2S-P2S5, Li2S-SiS2, Li2S-GeS2, Li2S-Al2S3, Li2S-SiS2-Li3PO4, Li2S-P2S5-GeS2, Li2S-Li2O-P2S5-SiS2, Li2S-GeS2-P2S5-SiS2, Li2S-SnS2-P2S5-SiS2, and the like.

[0162] Examples of the oxide-based inorganic solid electrolyte include NASICON types such as LiTi2(PO4)3, LiZr2(PO4)3, LiGe2(PO4)3, and perovskite types such as (La 0.5+x Li 0.5-3x )TiO3 and the like.

[0163] Examples of other lithium-based inorganic solid electrolyte materials include LiPON, LiNbO3, LiTaO3, Li3PO4, LiPO 4-x N x (where x is 0 < x ≤ 1), LiN, LiI, LISICON, and the like.

[0164] Examples of the polymer-based solid electrolyte include polymer materials showing ionic conductivity such as polyethylene oxide, polypropylene oxide, and copolymers thereof.

[0165] When the layer 120 is a current collector foil, the electrode laminate 100 of the positive electrode 110 and the current collector foil is widely used in electrochemical devices. The electrode laminate 100 including the positive electrode 110 and the current collector foil (layer 120) has the function of an electrode (positive electrode) as a whole. In that case, the positive electrode 110 may be adhered to the layer 120 in the positive electrode active material layer 12, and may be adhered to a separator, a solid electrolyte membrane, or the like in the adhesion layer 11 of the positive electrode 110.

[0166] The positive electrode 110 may have another member 130 on the surface of the positive electrode active material layer 12. An example of the other member 130 is a protective film that protects the electrode surface. The protective film is not particularly limited as long as it is made of a material that can protect the electrode from particles such as active material falling off the surface of the electrode, excessive reaction between the electrolyte and the electrode, and the like.

[0167] 4 is a schematic diagram (cross-sectional view) showing an electrode laminate 150 and a cell 500 having the electrode laminate 150. The electrode laminate 150 has the above-mentioned positive electrode 110, a first member 120 laminated on a first surface 110a of the positive electrode 110, and a second member 125 laminated on a second surface 110b of the positive electrode 110.

[0168] The first member 120 and the second member 125 are each one selected from the group consisting of a current collecting foil, a separator, and a solid electrolyte membrane, and correspond to the layer 120 in Fig. 3. Here, the first member 120 is a current collecting foil, and the second member is a solid electrolyte membrane.

[0169] The cell 500 has two electrode laminates 150, and the negative electrode 111 is sandwiched between the second member 125 of one electrode laminate 150A and the first member 120 of the other electrode laminate 150B. Moreover, the negative electrode 111 and the first member 120 (first member 120B) are laminated in this order on the second member 125 of the electrode laminate 150B.

[0170] The positive electrode 110 and the negative electrode 111 may be in direct contact with the first member 120 and the second member 125, or another member may be sandwiched between them. As the other members, the same ones as those described above can be used.

[0171] The cell 500 functions as a bipolar battery with the first component 120A as a positive terminal and the first component 120B as a negative terminal.

[0172] In the cell 500 configured as above, an electrode (positive electrode) formed from the above-mentioned original electrode film is used as the positive electrode 110. The positive electrode 110 has the functions of (a) having adhesiveness and (b) being usable as an electrode, so that the positive electrode 110 is formed by cutting it out from the original electrode film and then overlapping it with the first member 120 or the second member 125, thereby easily bonding the interface and easily laminating them.

[0173] [Electrochemical Devices] An electrochemical device includes the above-mentioned electrode laminate. Examples of the electrochemical device include a secondary battery and a capacitor.

[0174] Examples of secondary batteries include battery cells, modules made by connecting multiple cells, and packs made by connecting multiple modules. Electrochemical device products may include sensors and control circuits for preventing abnormalities such as overcharging and overdischarging. Leads (terminals) may be attached to the electrodes to electrically connect the battery to the outside.

[0175] The electrode laminate having a separator is used in a secondary battery having an electrolytic solution. An example of the electrolyte for a lithium ion secondary battery is a solution in which a lithium salt is dissolved in a non-aqueous solvent. Examples of the lithium salt include LiPF6, LiBF4, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)2NLi, etc. Examples of the non-aqueous solvent include carbonates (carbonic acid esters) such as ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).

[0176] An electrochemical device can be produced by combining the above-mentioned electrode laminate with other necessary members, for example, a separator, another electrode (counter electrode), etc. The counter electrode may be different from the electrode of this embodiment.

[0177] The container that houses the electrode stack can be made of a laminate film, metal, etc. The electrode stack may be disposed flat in the container, or may be housed in a curved, bent, wound, or other state.

[0178] [device] A module can be produced by connecting a plurality of cells. A pack can be produced by connecting a plurality of modules. Devices produced using batteries such as cells, modules, and packs include, but are not limited to, electronic devices such as smartphones, mobile phones, computers, and displays, and transportation devices such as electric vehicles and hybrid vehicles.

[0179] Although the preferred embodiment of the present invention has been described above with reference to the accompanying drawings, the present invention is not limited to the above embodiment. The shapes and combinations of the components shown in the above embodiment are merely examples, and various modifications can be made based on design requirements, etc., without departing from the spirit of the present invention. EXAMPLES

[0180] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.

[0181] (Examples 1 to 4, Comparative Examples 1 to 4) The materials used in the examples and comparative examples are as follows.

[0182] (binder) N150: Polyisobutylene, manufactured by BASF, model number N150, viscosity average molecular weight 2600000 6T: Polyisobutylene, manufactured by ENEOS, model number 6T, viscosity average molecular weight 30,000 PVdF: Polyvinylidene fluoride, Solvay, model number 5130

[0183] The above N150 corresponds to the first polyisobutylene in the present invention, and the above 6T corresponds to the second polyisobutylene in the present invention.

[0184] (Active material (positive electrode active material)) NCM: Manufactured by Xiamen Tungsten Co., Ltd. (XTC), model number HEC400

[0185] (Conductive material) AB: Acetylene black, manufactured by Alfa Aesar, model number 45527 KB: Ketjen Black, manufactured by Lion Specialty Chemicals, model number EC600JD

[0186] (Manufacture of film corresponding to adhesive layer) Each binder was dissolved in a solvent to prepare a solution having the following concentration. N150: 6% by weight in toluene 6T: 24% by weight toluene solution PVdF:6 mass% NMP solution

[0187] The obtained binder solution and conductive material were mixed in the binder equivalent ratio shown in Table 1 to form a slurry. Toluene was further added to adjust the viscosity. Furthermore, for some of the solutions, active material was mixed in the ratio shown in Table 1 with respect to the total amount of binder and conductive material.

[0188] The slurry was defoamed and passed through a sieve with 100 μm openings to obtain coating materials S1 to S9 for forming adhesive layers.

[0189] The resulting paints S1 to S8 were each applied to a release-treated PET film. The paints were applied at a constant volume depending on their specific gravity. In detail, paints S5 to S8 that did not contain active material were applied at 10 g / m2 (solid content). On the other hand, paints S1 to S4 that contained active material were applied at 20 g / m2 (solid content).

[0190] The resulting coating film was dried by heating at 90° C. for 5 minutes, and then pressed with a 10 μm spacer to adjust the thickness, to obtain films A1 to A8 corresponding to the adhesive layer.

[0191] [Table 1]

[0192] (Production of film corresponding to positive electrode active material layer) The conductive material (AB) was mixed with the PVdF solution in an amount equivalent to the binder, to prepare a slurry. Toluene was then added to adjust the viscosity.

[0193] The slurry was defoamed and passed through a sieve with 100 μm openings to obtain a coating material for forming a positive electrode active material layer.

[0194] The resulting coating was applied to a release-treated PET film at 3 mAh / cm 2 Specifically, the mass of the active material per unit area (applied mass, unit: g / cm) was calculated based on the target electrode capacity and the specific capacity (unit: mAh / g) of the active material used. 2 The coating was dried by heating at 120°C for 12 minutes. After drying, it was compressed with a roll press to a density of 3.2 g / cm. 3 The amount (mass) of the positive electrode active material was 2400 parts by mass relative to the total amount (100 parts) of the binder and the conductive material.

[0195] (Manufacturing electrode film rolls) The above-mentioned film corresponding to the positive electrode active material layer and the film corresponding to the adhesive layer were combined and laminated to prepare electrode film originals for the Examples and Comparative Examples. In the electrode film originals, the thickness of the positive electrode active material layer was 80-90% and the thickness of the adhesive layer was 10-20% (positive electrode active material layer + adhesive layer = 100%) of the total thickness of the electrode film original.

[0196] The physical properties of the prepared adhesive layer and electrode film were measured.

[0197] [Adhesive strength measurement] The measurement was performed by the method described above in (Method of measuring adhesive strength).

[0198] [Measurement of breaking strength] The breaking strength and elongation of the electrode film raw sheet, and the breaking strength and elongation of the electrode film raw sheet of the adhesive layer were measured by the method described above in (Method of measuring breaking strength and elongation).

[0199] [Resistance measurement] The resistance value of the original electrode film was measured by the method described above in (Method of measuring resistance value).

[0200] [Measurement of SOC-OCV value] The SOC-OCV value was measured by the method described above in (Method of measuring SOC-OCV value).

[0201] The evaluation results are shown in Tables 2 and 3. Table 2 shows the evaluation results of films A1 to A8, and Table 3 shows the evaluation results of the electrode film raw sheets obtained by combining films A1 to A8 with positive electrode active material layers.

[0202] [Table 2]

[0203] [Table 3]

[0204] The electrodes of Examples 1 to 4 all showed an adhesive strength of more than 0.05 N / cm at room temperature, suggesting that they could be easily attached to other members. In addition, the electrodes of Examples 1 to 4 had SOC-OCV values ​​of 18 times or more, confirming that they could be used as electrodes.

[0205] Furthermore, it was confirmed that the electrodes of Examples 1 to 4 were self-supporting.

[0206] In contrast, it was found that the electrode of Comparative Example 2 had low breaking strength and was difficult to stand on its own. Moreover, the electrode of Comparative Example 1 had insufficient adhesiveness at room temperature. Furthermore, the electrodes of Comparative Examples 3 and 4 had insufficient SOC-OCV values, which is believed to be due to the high resistance of the adhesive layer. In other words, it was confirmed that the electrodes of Comparative Examples 1 to 4 cannot be said to be self-supporting electrodes having adhesive properties, and thus cannot solve the problems of the present invention.

[0207] From the above results, it was found that the present invention is useful. [Explanation of symbols]

[0208] 1, 2... electrode film raw material, 10... release film, 11, 21... adhesive layer, 12, 22... positive electrode active material layer, 100, 150, 150A, 150B... electrode laminate, 110... electrode, 110a... first surface, 110b... second surface, 120, 120A, 120B... first member, 125... second member

Claims

1. An adhesive layer; a positive electrode active material layer laminated with the adhesive layer and containing a positive electrode active material, The adhesive layer includes a particulate conductive material and a binder, The binder includes a first polyisobutylene having a viscosity average molecular weight of 1,000,000 or more, and a second polyisobutylene having a viscosity average molecular weight of 10,000 or more and 100,000 or less, the conductive material is a carbon material, The adhesive layer is an electrode film raw material containing, relative to a total of 100 mass% of the conductive material and the binder, 15 mass% or more and 25 mass% or less of the conductive material, 25 mass% or more and 50 mass% or less of the first polyisobutylene, and 30 mass% or more and 60 mass% or less of the second polyisobutylene.

2. 2 . The electrode film base material according to claim 1 , which has a breaking strength of 0.4 MPa or more, measured by the following measurement method, and an elongation percentage at the time of exhibiting said breaking strength of 3% or more and 7% or less. (Measurement method) The electrode film raw material was cut to a size of 15 mm in width and 50 mm in length to obtain a test piece, and the breaking strength was determined as the strength at 75% of the maximum stress when the test piece was measured under conditions of a chuck distance of 30 mm and a tensile speed of 100 mm / min.

3. 3 . The electrode film substrate according to claim 1 , wherein the adhesive layer has a breaking strength of 0.3 MPa or more, as measured by the following measurement method, and an elongation percentage at the time of exhibiting the breaking strength of 30% or more. (Measurement method) The electrode film raw material was cut to a size of 15 mm in width and 50 mm in length to obtain a test piece, and the breaking strength was determined as the strength at 75% of the maximum stress when the test piece was measured under conditions of a chuck distance of 30 mm and a tensile speed of 100 mm / min.

4. 3. The electrode film substrate according to claim 1, wherein the adhesive layer has an adhesive strength of 0.05 N / cm or more in a 90° peel test performed according to the following measurement method. (Measurement method) The adhesive layer side of a test piece 15 mm wide and 50 mm long cut from the electrode film roll is attached to the center of an Al foil 15 mm wide and 60 mm long. A paper tape longer than the test piece is attached to the side of the test piece opposite the adhesive layer side, and the strength is measured when the paper tape protruding from the test piece is gripped and the test piece together with the paper tape is peeled off at 90° at a speed of 20 mm / min. The same measurement is performed three times, and the arithmetic average of the measured values ​​is taken as the adhesive strength. (Lamination conditions) Roll lamination was performed under a pressure of 8.6 kg / cm and a speed of 1 m / min in a 25°C environment.

5. The electrode film substrate according to claim 1 or 2, wherein a release film is laminated on the adhesive layer.

6. An electrode made from the electrode film base material according to claim 1 or 2.

7. An electrode according to claim 6; and any one selected from the group consisting of a current collector foil, a separator, and a solid electrolyte membrane.

8. An electrode according to claim 6; a first member laminated on a first surface of the electrode; a second member laminated on a second surface of the electrode, The electrode laminate, wherein the first member and the second member are each any one selected from the group consisting of a current collector foil, a separator, and a solid electrolyte membrane.

Citation Information

Patent Citations

  • Secondary battery electrode, secondary battery, and manufacturing method thereof

    JP2019169444A